Mandibular Fixed Prosthesis With a 3D-Printed Subperiosteal Implant: A Case Report - Kizilkaya, Ayse Rencber; Sagsoz, Asli; Dundar, Serkan; Bozoglan, Alihan; Duger, Nurullah; Ozcan, Erhan Cahit (Knowledgeworks Global Ltd-Kgl, 2024)
This case report aims to present the successful restoration of the atrophic partially edentulous posterior mandible using custom-made subperiosteal implants. The fixed prosthesis restoration was achieved using computer-aided design and computer-aided manufacturing technologies and 3D metal printing methods. The partially edentulous 58-year-old patient expressed a preference not to undergo bone augmentation procedures. The patient with teeth in the anterior mandible was treated with 2 separate custom-made subperiosteal implants. A custom-made implant was fabricated from sintered titanium using machined subperiosteal implants with a universal external connection. Subperiosteal implants offer several advantages over conventional bone grafting plus intraosseous implant placement techniques, such as the simple, 1-step procedure for atrophic jaws, streamlining the treatment process and reducing the overall time involved. Treatments using subperiosteal implants can be an alternative solution for individuals with severely atrophic jaws. Longer term studies in a larger sample are warranted to corroborate previous reports.
Keywords: atrophic jaws; subperiosteal implants; custom-made; 3D printed